Secure massive IoT using hierarchical fast blind deconvolution - Wunder, Gerhard; Roth, Ingo; Fritschek, Rick; Gros, Benedikt; Eisert, Jens (2018 IEEE Wireless Communications and Networking Conference Workshops, WCNCW 2018, 2018)
The Internet of Things and specifically the Tactile Internet give rise to significant challenges for notions of security. In this work, we introduce a novel concept for secure massive access. The core of our approach is a fast and low-complexity blind deconvolution algorithm exploring a bi-linear and hierarchical compressed sensing framework. We show that blind deconvolution has two appealing features: 1) There is no need to coordinate the pilot signals, so even in the case of collisions in user activity, the information messages can be resolved. 2) Since all the individual channels are recovered in parallel, and by assumed channel reciprocity, the measured channel entropy serves as a common secret and is used as an encryption key for each user. We will outline the basic concepts underlying the approach and describe the blind deconvolution algorithm in detail. Eventually, simulations demonstrate the ability of the algorithm to recover both channel and message. They also exhibit the inherent trade-offs of the scheme between economical recovery and secret capacity.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 5G; Blind deconvolution; Compressed sensing; Hierarchical sparsity; Massive IoT; Physical layer security